(untitled) (International Seven Journal of Health Research, 2024)
Phenol chemical peeling is considered a deep peeling that promotes facial rejuvenation, an aggressive method, promoting the exchange of several layers of the epidermis and dermis generating local re-epithelialization, leading to intense cell renewal, which helps in rejuvenation, stimulating its collagen, and consists of accelerating the exfoliation of the skin, through the use of chemical agents (acids), accelerating the speed of cell renewal.